Al-Kulaini's Canonization of Al-Kafi - Kharis Nugroho (Universitas Darussalam Gontor, 2022)
This study discusses the history of the authority of the kitab al-Kāfī in the canonization frame. The authority of a religious text is not formed instantly, but there are factors behind it, like the kitab al-Kāfī, which is the best book of hadith among the kutub al-arba'ah in the Shia community. These factors involve many parties and run for a long time. To see the process of canonizing the authority of kitab Al-Kāfī, this study uses Keith Ward's theory about the periodization of the development of religious scriptures in the world. This study discovers three findings. First, the condition of the Shia community which experienced a crisis of hadith literature in the 4th century made the book of Al-Kāfī quickly gain high authority because it became the need of society at that time. In addition, there are Shia scholars mainly from the Akhbāriah group who are aggressive in spreading, strengthening, and sanctifying the authenticity of the hadith of al-Kāfī. Kulaini's position as a marja' taqlid and the perfection of the systematic writing of al-Kāfī also helped strengthen his authority. Even al-Kāfī received recognition from Imam al-Mahdi (through his messenger), which is a book that meets the needs of the Shia community. Second, there are those rulers who support the canonization process of al-Kāfī's authority, including the rulers of Buwaihiah in the mutaqaddimīn era, the rulers of Ṣafawiah in the mutaakhirīn era, and perfected in the mu'aṣirīn era by the government of the Shia Republic of Iran.